Safety and diagnostic accuracy of percutaneous biopsy in upper tract urothelial carcinoma. (20th October 2014) - Huang, Steven Y.; Ahrar, Kamran; Gupta, Sanjay; Wallace, Michael J.; Ensor, Joe E.; Krishnamurthy, Savitri; Matin, Surena F.
Abstract : Objective: To assess the diagnostic accuracy and safety of percutaneous biopsy for upper tract urothelial carcinoma (UTUC). Patients and Methods: From 2002 to 2013, 26 upper tract lesions in 24 patients (20 men; median [range] age 67.8 [51.7–85.9] years) were percutaneously biopsied. Analysis was separated based on lesion appearance: (i) mass infiltrating renal parenchyma, (ii) filling defect in the collecting system, (iii) urothelial wall thickening. We tracked immediate complications and tract seeding on follow‐up imaging. Results: Of the 26 upper tract lesions, 15 (58%) were masses infiltrating the renal parenchyma (mean [range] size 5.4 [1.1–14.0] cm), six (23%) were urothelial wall thickenings (mean [range] size 0.8 [0.4–1.1] cm), and five (19%) were filling defects within the renal pelvis or calyx (mean [range] size 2.7 [1.0–4.6] cm). Definitive diagnosis of UTUC was made by biopsy in 22 of 26 lesions (85%). Biopsy characterised 14 of 15 infiltrative masses and five of five filling defects; biopsy characterised three of six cases of urothelial wall thickening. CT follow‐up was available for 19 patients (73%) at a median (range) of 13.6 (1.0–98.9) months. Three patients (11%) developed recurrence in the nephrectomy bed at 5.6, 9.7, and 29.0 months after biopsy; none were attributed to tract seeding after independent review, because recurrence was remote from the biopsy site. Conclusion: Percutaneous biopsy is effective for diagnosis of UTUC, providing tissue diagnosis in 85% of cases. While case reports cite a risk of tract seeding, no cases of recurrence were definitely attributable to percutaneous biopsy. Thus, for upper tract urothelial lesions, which are not amenable to endoscopic biopsy, percutaneous biopsy is a safe and effective technique.